1981
DOI: 10.1210/jcem-53-4-883
|View full text |Cite
|
Sign up to set email alerts
|

Spermatic and Peripheral Plasma Concentrations of Testosterone and Androstenedione in Prepubertal Boys

Abstract: Spermatic and peripheral plasma concentrations of testosterone (T) and androstenedione (A) have been measured in prepubertal boys affected by inguinal hernia (group I; n = 7) and unilateral undescended testis (group II; n = 18). Mean (+/- SE) spermatic T concentrations (47.7 +/- 14.8 ng/dl in group I; 36.3 +/- 3.4 ng/dl in group II) were significantly different from mean peripheral T concentrations (9.8 +/- 2.1 ng/dl in group I; 9.3 +/- 0.9 ng/dl in group II) in both groups (P less than 0.05 and P less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…In our subjects plasma A remained unchanged, in agreement with Forti et al (25), who found an inconstant…”
Section: Discussionsupporting
confidence: 93%
“…In our subjects plasma A remained unchanged, in agreement with Forti et al (25), who found an inconstant…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the male rhesus monkey appears to be at least quantitative¬ ly different from man, since prepubertal children remain responsive to GnRH administration, at least in terms of FSH release, and one can usually observe values of serum FSH above the normal prepubertal range in children with congenital or traumatic anorchia (Winter & Faiman 1972). Fur¬ thermore, in boys there is evidence for continued low-level secretion of sex steroids throughout the juvenile period (Forti et al 1981). Therefore, it seems likely, in the human male, that central inhibition of gonadotropin release before puberty may be supplemented by some degree of steroidmediated feedback inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the early activation of Leydig cell precursors which are capable of responding to luteinizing hormone (LH) stimulation with testosterone secretion ( Chemes et al ., 198 5, 1992; Cigorraga et al ., 1994 ; Chemes, 1996). These precursors are responsible for testosterone production during infancy when differentiated Leydig cells are absent from the intertubular spaces ( Forti et al ., 1981 , Chemes, 1996). Leydig cell precursors can be defined on the basis of their ability to produce discrete amounts of testosterone and/or to exhibit typical Leydig cell markers such as 3β hydrosysteroid dehydrogenase ( Pelliniemi et al ., 1981 ; Chemes et al ., 1992 ; Cigorraga et al ., 1994 ).…”
Section: Leydig Cell Changes In Infancymentioning
confidence: 99%